Establishing a Guideline and Decision-Making Approach for UAE Solar Assets Waste Management by Utilizing PVsyst - Al−Ali, Amel Khalid Ali (2024)
This open access book presents contributions on a wide range of scientific areas originating from the BUiD Doctoral Research Conference (BDRC 2023)